Dynamic Evaluation Method of Lower Limb Joint Alignment with Parallel Feet (MADAAMI-P): Content validation and Reproducibility - Maiane Almeida do Amaral; Cláudia Tarragô Candotti; Isis Juliene Rodrigues Leite Navarro; Kaanda Nabilla Souza Gontijo; Taís Regina Fiegenbaum; Gabriela Cristina dos Santos; Jefferson Fagundes Loss (Motricidade, 2019)
Neutral static alignment, normal movement and a satisfactory segmental interrelationship are described as significant factors in normal asymptomatic function and, when altered, increase the risk of lesions in the lower limbs. It is important to focus on the early identification of joint misalignments. Thus, the present study aims at developing, validating the content developed and confirming the reproducibility of the Dynamic Evaluation Method of Lower Limb Joint Alignment with Parallel Feet (MADAAMI-P), a simple video-based evaluation method using surface markers and a score sheet. The study was carried out in three stages: (1) the Dynamic Evaluation Method of Lower Limb Joint Alignment for dancers (MADAAMI) was adapted; (2) the content validity of the score sheet used  in MADAAMI-P was checked; and (3) the intra- and inter-rater reproducibility were evaluated. Cohen's Kappa coefficient and the Intraclass Correlation Coefficient (ICC) were used in the statistical analysis to analyze the categories of the score sheet criteria and sum of the scores (α <0.05). The results showed that MADAAMI-P presents content validity satisfactory.